Acute Kidney Injury in Patients with Stroke Presenting to a Tertiary Care Hospital, Hyderabad - Zubaida, .; Das, Bhagwan; Raheela, .; Salma, .; Aftab, Taimoor; Kumar, Haresh (Biological and Clinical Sciences Research Journal, 2025)
Acute kidney injury (AKI) in acute stroke is now widely recognized as a common and serious complication with major clinical implications. It contributes independently to worse functional outcomes and is a strong predictor of in-hospital, short-term, and long-term mortality, regardless of underlying comorbidities and stroke severity. Objective: To determine the frequency of acute kidney injury in patients presenting with acute stroke at a tertiary care hospital. Methods: This cross-sectional descriptive study was conducted for 3 months from 14-02-2025 to 13-05-2025, at the Nephrology ward of Liaquat University Hospital (LUH), Hyderabad. Patients aged 40–85 years presenting with acute stroke were enrolled, and those with chronic kidney disease, recurrent stroke, alcohol use, or intravenous drug abuse were excluded. Demographic data, including age, gender, smoking status, and residential status (rural or urban), were recorded. Stroke type was determined by reviewing computed tomography (CT) scans and classified as ischemic or hemorrhagic. Primary outcome, the occurrence of acute kidney injury (AKI), was also recorded. Results: A total of 95 participants were included, with a mean age of 57.97 ± 8.62 years. AKI was identified in 34.7% of stroke patients. Patients suffering from ischemic stroke demonstrated a markedly greater occurrence of acute kidney injury (45.9%) in contrast to those experiencing hemorrhagic stroke (14.7%) (p=0.002). AKI also showed statistically significant associations with diabetes mellitus (p=0.046), smoking (p=0.001), and hypertension (p=0.002). Conclusion: AKI is a prevalent and serious concern among acute stroke patients, especially in those with ischemic stroke, diabetes mellitus, hypertension, and smoking history.